2020
DOI: 10.1128/mra.00065-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Clostridium perfringens netB -Positive Strain 2016TE7641_69, Isolated from the Intestine of a Diseased Turkey in Italy

Abstract: Here, we report the complete genome sequence of Clostridium perfringens 2016TE7641_69, isolated from the intestine of a turkey reared in a conventional poultry flock located in central Italy, where animals were showing enteric disorders suggesting subclinical necrotic enteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Many plasmid-containing strains have recently been reported. Profeta et al reported two plasmids in the C. perfringens netB positive strain 2016TE7641_69 isolated from the intestine of a diseased turkey in Italy 16 . In C. www.nature.com/scientificreports/ perfringens CBA7123 isolated from humans, Kim et al identified a 46,640-bp plasmid (with a G + C content of 27.1%) 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Many plasmid-containing strains have recently been reported. Profeta et al reported two plasmids in the C. perfringens netB positive strain 2016TE7641_69 isolated from the intestine of a diseased turkey in Italy 16 . In C. www.nature.com/scientificreports/ perfringens CBA7123 isolated from humans, Kim et al identified a 46,640-bp plasmid (with a G + C content of 27.1%) 17 .…”
Section: Discussionmentioning
confidence: 99%